2011
DOI: 10.1016/j.jprot.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial proteins with cleaved or uncleaved signal peptides of the general secretory pathway

Abstract: Correct protein compartmentalization is a key step for molecular function and cell viability, and this is especially true for membrane and externalized proteins of bacteria. Recent proteomic reports of Bacillus subtilis have shown that many proteins with Sec-like signal peptides and absence of a transmembrane helix domain are still observed in membrane-enriched fractions, but further evidence about signal peptide cleavage or soluble protein contamination is still needed. Here we report a proteomic screening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 32 publications
14
141
1
Order By: Relevance
“…Another important feature of the M. tuberculosis Rv3852 protein is its subcellular localization, since it was detected only in the cell membrane and not in the other subcellular compartments or in the culture supernatant (Fig. 2), as reported earlier in a proteomic survey (35). This localization is compatible with a role for Rv3852 in chromosome segregation during cell division, as proposed by Ghosh et al (21).…”
Section: Discussionsupporting
confidence: 85%
“…Another important feature of the M. tuberculosis Rv3852 protein is its subcellular localization, since it was detected only in the cell membrane and not in the other subcellular compartments or in the culture supernatant (Fig. 2), as reported earlier in a proteomic survey (35). This localization is compatible with a role for Rv3852 in chromosome segregation during cell division, as proposed by Ghosh et al (21).…”
Section: Discussionsupporting
confidence: 85%
“…A subsequent literature search revealed that almost all further selected IVE-TB proteins (14 of the 16) have been identified previously in M. tuberculosis proteomic studies, confirming the protein expression of the M. tuberculosis genes identified in our study (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) (Table III). Indeed, we observed that M. tuberculosis- FIGURE 3.…”
Section: Immunogenicity Of Newly Identified Ive-tb Agssupporting
confidence: 87%
“…Indeed, in both Grampositive and -negative bacteria, this particular residue is often substituted for leucine, an amino acid with an even longer side chain than valine. The second SNP in isolate HN878-27 is a T730C transition that results in the substitution of glutamic acid for glycine (E244G) in Rv1215c, a gene which encodes a hypothetical protein found in the membrane fraction of M. tuberculosis (41,42). As the function of Rv1215c is unknown at present, it is difficult to assess whether a mutation in this protein could have an effect on virulence.…”
Section: Resultsmentioning
confidence: 99%